The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1002/ajhb.23106
|View full text |Cite
|
Sign up to set email alerts
|

Reproductive health, obesity, and cardiometabolic risk factors among Samoan women

Abstract: The prevalence of menstrual irregularity and PCOS are less than hypothesized given the high levels of adiposity in this population. Nevertheless, Samoan women with menstrual irregularity and other features of PCOS have significantly poorer metabolic health.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
0
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 52 publications
1
0
0
1
Order By: Relevance
“…This is in line with research conducted in the Madura tribe that the PCOS group had a BMI in the obesity category at the age of >30 years. The results of this study also showed in the PCOS group, BMI were in the 50% obesity category and 50% normal, while in the BMI control group, there were in the normal categories, signs, and symptoms of PCOS one of which is irregular menstruation due to obesity, this is in accordance with the Mahedia 2018 study, said that women who are obese will increase the occurrence of irregular menstruation causing infertility [13,14].…”
Section: Distribution Of Clinical Symptoms In Study Subjectssupporting
confidence: 88%
“…This is in line with research conducted in the Madura tribe that the PCOS group had a BMI in the obesity category at the age of >30 years. The results of this study also showed in the PCOS group, BMI were in the 50% obesity category and 50% normal, while in the BMI control group, there were in the normal categories, signs, and symptoms of PCOS one of which is irregular menstruation due to obesity, this is in accordance with the Mahedia 2018 study, said that women who are obese will increase the occurrence of irregular menstruation causing infertility [13,14].…”
Section: Distribution Of Clinical Symptoms In Study Subjectssupporting
confidence: 88%
“…Pada usia < 20 tahun, ukuran uterus belum mencapai ukuran yang normal untuk kehamilan, sehingga kemungkinan terjadinya gangguan dalam kehamilan seperti preeklampsia menjadi lebih besar. Pada usia > 35 tahun terjadi proses degeneratif yang mengakibatkan perubahan sruktural dan fungsional yang terjadi pada pembuluh darah perifer yang bertanggung jawab terhadap perubahan tekanan darah, sehingga lebih rentan mengalami preeclampsia (16) .…”
Section: Zakkiyatus Zainiyah Et Al Factors Associated With the Incide...unclassified